2013
DOI: 10.3920/bm2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of diarrhoea with Saccharomyces boulardii in children with acute lower respiratory tract infections

Abstract: The aim of this study was to determine whether Saccharomyces boulardii prevents and treats diarrhoea and antibiotic-associated diarrhoea (AAD) in children. A total of 333 hospitalised children with acute lower respiratory tract infection were enrolled in a 2-phase open randomised controlled trial. During the 1st phase, all children received intravenous antibiotics (AB). They were randomly allocated to group A (S. boulardii 500 mg/day + AB, n=167) or group B (AB alone, n=166) and followed for 2 weeks. Diarrhoea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 21 publications
1
49
0
4
Order By: Relevance
“…Although some studies demonstrated the effectiveness of S. boulardii for resetting alterations caused by antibiotic treatment [37,38,39], we found no microbial protective effects in this study; the results of the group that received S. boulardii were identical to those of the group that received amoxicillin alone (i.e. an increase in body fat was observed).…”
Section: Discussionsupporting
confidence: 47%
“…Although some studies demonstrated the effectiveness of S. boulardii for resetting alterations caused by antibiotic treatment [37,38,39], we found no microbial protective effects in this study; the results of the group that received S. boulardii were identical to those of the group that received amoxicillin alone (i.e. an increase in body fat was observed).…”
Section: Discussionsupporting
confidence: 47%
“…Most reports show a clinical benefit of S. boulardii in decreasing the duration of diarrhoea regardless of the cause and thus reducing hospital stay resulting in social and economic benefits [7,33,56,57,58]. Administration of S. boulardii has shown positive effects for patients with irritable bowel syndrome [59], preventing and treating relapses of inflammatory bowel disease and for treating moderate symptoms of ulcerative colitis [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…Figure S1 documents the identification process for eligible trials. In addition to the previously identified five RCTs, 16 new trials were included . Except for three trials published in Chinese, Portuguese and Spanish for which the translation was obtained, all of the remaining trials were published in English.…”
Section: Resultsmentioning
confidence: 99%